Addressing Hyperconnected Society’s Challenges Through Laozi–Zhuangzi Thought - Dugsam Kim; Taesoo Kim (Religions)
This paper examines the challenges of our hyperconnected society through the lens of Daoist philosophy, specifically drawing on the thoughts of Laozi and the Zhuangzi. This study begins by analyzing the broad implications of hyperconnectivity in contemporary society, highlighting how unprecedented levels of interconnection shape modern human experience. The analysis identifies three critical challenges in our hyperconnected world: the individual cognitive level (where connected subjects experience confirmation bias and cognitive dissonance); the structural level (where systemic forces diminish individual autonomy and create unpredictable outcomes); and the amplified social level (where the interaction between individual and structural factors intensifies social division, isolation, systemic risks, and cascading failures). This paper approaches these challenges through three key Daoist concepts: Dao as the foundational principle of reality, Qi as the underlying logic of interconnection, and the complementary principles of Wu-wei (non-action) and Ziran (self-so-ness) as frameworks for managing desire. These concepts yield two crucial insights: the need to deepen our understanding of connectivity’s practical dimensions and the importance of maintaining critical distance between means and ends through persistent questioning of fundamental principles. As technological advancement and material concerns increasingly dominate society, Daoist philosophy offers both a warning about the potential loss of human essence and practical guidance for maintaining purposeful awareness through Wu-wei and Ziran. The concept of Qi further illuminates humanity’s fundamental embeddedness in universal interconnection. This paper concludes by proposing ways to bridge theory and practice, emphasizing expanded awareness of connectivity, philosophical inquiry into essence, and the enduring relevance of humanistic wisdom.